Autoriti agama di Malaysia: kedudukan dan kritikan - Nur Farhana Abdul Rahman,; Nur Solehah Shapiee, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to highlight the view of G25 towards the religious authority in Malaysia. G25 is seen to have its own definitions pertaining to Islamic religious authority which has led this group to voice out several issues and criticism towards religious authority. These issues and criticism have caused some controversy and confusion among Muslim communities in Malaysia. Hence, this study aims to analyze the views and key issues raised by G25 about religious authority and their justification. This is qualitative study using content analysis methodology from various sources in the form of books, journals, articles and electronic materials related to this topic and supported by the interview with one of their members in elaborating their views on the issues. The findings show that G25 claimed that they are not rejecting religious authority completely but rejects the approach of the procedure used by religious authority in implementing Syariah Law. In view of that, G25 demands that the implementation of Syariah Law must be accordance with the Federal Constitution, which they believe it is secular. Hence, the interpretation of the texts of the Holy Qur'an and the Sunnah as the basis of law-making especially regarding of Syariah Laws should be re-examined in the method of interpretation.